Fabrication of porous Fe2O3/PTFE nanofiber membranes and their application as a catalyst for dye degradation. Issue 39 (4th April 2016) - Kang, Weimin; Li, Fu; Zhao, Yixia; Qiao, Chunmei; Ju, Jingge; Cheng, Bowen
Abstract : Novel porous polytetrafluoroethylene (PTFE) nanofiber membranes containing Fe2 O3 (Fe2 O3 /PTFE), used as a heterogeneous catalyst, were prepared via a three-step method by electrospinning, immersion and calcination. Abstract : Novel porous polytetrafluoroethylene (PTFE) nanofiber membranes containing Fe2 O3 (Fe2 O3 /PTFE), used as a heterogeneous catalyst, were prepared via a three-step method by electrospinning, immersion and calcination. The morphology and structure of porous Fe2 O3 /PTFE were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and X-ray diffractometer (XRD). The effects of the thickness of the as-spun nanofiber membrane, the immersion time and impregnating solution concentration on the content of Fe2 O3 which was the active component were discussed. The degradation of Acid Red with hydrogen peroxide catalyzed by the porous Fe2 O3 /PTFE under UV irradiation was investigated. UV-vis and ESR techniques provided an insight into the nature of the degradation products and the formed active species. The results showed that Fe2 O3 was successfully supported on the surface of porous PTFE nanofibers. The porous Fe2 O3 /PTFE nanofiber membrane prepared under the optimized parameters possessed high photocatalytic activity without any dye adsorption and could be recycled by simple filtration.